Molecular chaperones are nanomachines that catalytically unfold misfolded and alternatively folded proteins - Mattoo, Rayees U. H. (Springer Basel, 2014)
By virtue of their general ability to bind (hold) translocating or unfolding polypeptides otherwise doomed to aggregate, molecular chaperones are commonly dubbed “holdases”. Yet, chaperones also carry physiological functions that do not necessitate prevention of aggregation, such as altering the native states of proteins, as in the disassembly of SNARE complexes and clathrin coats. To carry such physiological functions, major members of the Hsp70, Hsp110, Hsp100, and Hsp60/CCT chaperone families act as catalytic unfolding enzymes or unfoldases that drive iterative cycles of protein binding, unfolding/pulling, and release. One unfoldase chaperone may thus successively convert many misfolded or alternatively folded polypeptide substrates into transiently unfolded intermediates, which, once released, can spontaneously refold into low-affinity native products. Whereas during stress, a large excess of non-catalytic chaperones in holding mode may optimally prevent protein aggregation, after the stress, catalytic disaggregases and unfoldases may act as nanomachines that use the energy of ATP hydrolysis to repair proteins with compromised conformations. Thus, holding and catalytic unfolding chaperones can act as primary cellular defenses against the formation of early misfolded and aggregated proteotoxic conformers in order to avert or retard the onset of degenerative protein conformational diseases.